ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL TEOREMA PHYTAGORAS BERDASARKAN KRITERIA NEWMAN PADA SISWA KELAS VIII DI SMP NEGERI 8 SAWAHLUNTO - Ira Dya Fitri, Desi; Rahmi, Rahmi; Delyana, Hafizah (Department of Mathematics Education, Universitas Kuningan, 2025)
This research aims to find out what mistakes students make in solving mathematics questions in class VIII at SMP Negeri 8 Sawahlunto. This research method uses qualitative research with descriptive methods. The subjects of this research were 15 students, the technique for selecting research subjects used Purposive Sampling, the instruments used in data collection were tests, interviews and documentation. The test results were analyzed based on Newman's criteria with the criteria reading error (re), comprehension error (ce), transformation error (te), process skill error (pse) and encoding error (ee). After that, students were interviewed based on the types of errors the students made. The results of the research showed that the types of errors made by students were: (1) Reading Error (RE) of 29 errors, namely students were not careful in reading the words or important information in the question, (2) Comprehension Error (CE) of 34 errors, namely students were not careful, forgot and were confused in writing and determining what was known and asked in the question, (3) Transformation Error (TE) was 13 errors, namely students did not pay attention to the formula that had been made, then students were less careful in using the correct formula, (4) Process Skill Error (PSE) as many as 7 errors, (5) Encoding Error (EE) as many as 31 errors, namely the result of previous errors in the calculation process so that students were in a hurry to work out the final answer.